The causal relationship between inflation and inflation expectations in the United Kingdom - Roger Kelly (Bank of England, External Monetary Policy Committee Unit, 2008)
Two major events have affected the monetary regime in the United Kingdom in recent years, namely the introduction of inflation targeting, and the granting of operational independence to the Bank of England. In this paper we examine what impact, if any, these events have had on inflation expectations. A series of Granger causality tests are used in order to examine the causal relationship between a measure of prices and inflation expectations. We find evidence that the introduction of inflation targeting caused both the general public and professionals to anchor their expectations, rather than basing them on current RPI inflation.
Keywords: 330